3D augmented reality visualization for navigated osteosynthesis of pelvic fractures „3D-augmented-reality“-Visualisierung für die navigierte Osteosynthese von Beckenfrakturen - Befrui, N.; Fischer, M.; Fuerst, B.; Lee, S. -C.; Fotouhi, J.; Weidert, S.; Johnson, A.; Euler, E.; Osgood, G.; Navab, N.; Boecker, W. (Unfallchirurg, 2018)
Background: Despite great advances in the development of hardware and software components, surgical navigation systems have only seen limited use in current clinical settings due to their reported complexity, difficulty of integration into clinical workflows and questionable advantages over traditional imaging modalities. Objectives: Development of augmented reality (AR) visualization for surgical navigation without the need for infrared (IR) tracking markers and comparison of the navigation system to conventional imaging. Material and methods: Novel navigation system combining a cone beam computed tomography (CBCT) capable C‑arm with a red-green-blue depth (RGBD) camera. Testing of the device by Kirschner wire (K-wire) placement in phantoms and evaluation of the necessary operating time, number of fluoroscopic images and overall radiation dose were compared to conventional x‑ray imaging. Results: We found a significant reduction of the required time, number of fluoroscopic images and overall radiation dose in 3D AR navigation in comparison to x‑ray imaging. Conclusion: Our AR navigation using RGBD cameras offers a flexible and intuitive visualization of the operating field for the navigated osteosynthesis without IR tracking markers, enabling surgeons to complete operations quicker and with a lower radiation exposure to the patient and surgical staff.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computer assisted surgery; Feasibility studies; Kirschner wires; Radiation exposure; Time factors